1995
DOI: 10.1590/s0074-02761995000100003
|View full text |Cite
|
Sign up to set email alerts
|

Degree of host-parasite compatibility between Schistosoma mansoni and their intermediate molluscan hosts in Brazil

Abstract: The compatibility of Biomphalaria tenagophila, B. straminea and B. glabrata from Minas Gerais with different strains of Schistosoma mansoni was evaluated using the method of Frandsen (1979b) in standardized experiments. One hundred and fifty of each species of snail were individually exposed in the laboratory to 50 miracidia of S. mansoni lines LE, SJ and AL. The cercariae from the infected snails were counted and used to calculate TCP/100 indices, which were compared with those of Frandsen (1979b). For B. ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
3
14
1
1
Order By: Relevance
“…Compatibility Index assessments using three strains of S. mansoni Table 1 Molluscicidal activity of commercial ivermectin (a mixture of ivermectin B 1a (1) and B 1b (2)) against B. glabrata, B. tenagophila and B. straminea (LE, SJ and AL) demonstrating that B. straminea displays by far the lowest levels of infection. 20 We found ivermectin to be less potent than previously reported, B. glabrata appearing 5-fold less susceptible to ivermectin in comparison with the data presented by Matha and Weiser. It is therefore important to emphasize our finding that only one of the two constituents of IVM appears to have molluscicidal properties.…”
Section: Discussionsupporting
confidence: 70%
“…Compatibility Index assessments using three strains of S. mansoni Table 1 Molluscicidal activity of commercial ivermectin (a mixture of ivermectin B 1a (1) and B 1b (2)) against B. glabrata, B. tenagophila and B. straminea (LE, SJ and AL) demonstrating that B. straminea displays by far the lowest levels of infection. 20 We found ivermectin to be less potent than previously reported, B. glabrata appearing 5-fold less susceptible to ivermectin in comparison with the data presented by Matha and Weiser. It is therefore important to emphasize our finding that only one of the two constituents of IVM appears to have molluscicidal properties.…”
Section: Discussionsupporting
confidence: 70%
“…Parasites and hosts -The S. mansoni (LE strain) life cycle was maintained using B. glabrata (Barreiro de Cima strain) snails as intermediate hosts and Swiss mice as definitive hosts, according to Pellegrino and Katz (1968) and Souza et al (1995).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Thirty days post-infection the snails were exposed to ar-tificial light for 1 h to verify the shedding of cercariae (Souza et al 1995). The snails shedding cercariae were divided into two groups (infected snail or infected snails treated with PZQ).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…Differences in susceptibility/resistance occur not only intraspecifically (Souza et al 1995b), but have been demonstrated between different snail species, such as B. glabrata, B. tenagophila and B. straminea (Barbosa 1975, Souza et al 1995a.…”
mentioning
confidence: 99%